Karandu (Gong): History, Functions, and Symbols in the Life of the Tolaki People in 17th -20th Century Southeast Sulawesi - Akhmad Marhadi; Syahrun Syahrun; Basrin Melamba; Marwati Marwati; Hayari Hayari (IHiS (Indonesian Historical Studies))
By applying the historical method, this study aims to explain the history of the development of the gong (karandu) in Southeast Sulawesi and how the gong changes its function and symbol. The karandu entry into Tolaki estimated about the 13th century AD, originated from Java (Majapahit) and then experienced development during the Wolio kingdom. Furthermore, the acquisition of karandu occurred between the 16th and 20th centuries from outside traders as well as through shipping and trade with the natives. Gongs at that time were used as royal and confidential treasures of high value, art, ceremonies, social status, and many more. The gong evolved to communicate in particular situations, such as codes or signs of danger, meetings, grief, etc. The function of adat as a customary object in the moruhu owuku/ mooli anakia custom (buying nobility). The traditional object in marriage was called tawa-tawa sara (traditional gong), then replaced with money (nililima/ nilungga). The religious function was used when the Mokoweadeath ceremony was beaten when death occurs until the body was delivered to the cemetery. This function remained limited to the descendants of the nobility, the rich, or those with positions. In the past, gongs had an economic role with high prices and values as a criterion of prosperity. Several symbols were contained in the gong: social status, classic, unity, religious, and communication. Nowadays, they are no longer considered valuable objects.